2020
DOI: 10.1016/j.oret.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of Proliferative Diabetic Retinopathy Using OCT

Abstract: To present the routine use of optical coherence tomography (OCT) and OCT angiography (OCTA) for the objective diagnosis and monitoring of proliferative diabetic retinopathy (PDR).Design: Retrospective observational case series. Subjects:Patients with diabetic retinopathy imaged using a standardized PDR-protocol Methods: Patients routinely imaged with a standardized PDR-protocol between March 2017 and January 2019 were included. This included a 12x9 mm structural OCT volume centered on the macula and a 6x6 mm O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…Most NVE and NVD will be detected on careful clinical examination and are usually clearly visible on FFA. OCT examination can also be very helpful to determine if NV are present (at the posterior pole, where such imaging is possible) in doubtful cases by the presence of pre-retinal hyperreflective material [188]. OCT-A can also be very helpful in assessing areas of capillary non-perfusion and show flow within the new vessels.…”
Section: Clinical Assessment For Pdrmentioning
confidence: 99%
“…Most NVE and NVD will be detected on careful clinical examination and are usually clearly visible on FFA. OCT examination can also be very helpful to determine if NV are present (at the posterior pole, where such imaging is possible) in doubtful cases by the presence of pre-retinal hyperreflective material [188]. OCT-A can also be very helpful in assessing areas of capillary non-perfusion and show flow within the new vessels.…”
Section: Clinical Assessment For Pdrmentioning
confidence: 99%
“…The highest rate of detection of NVDs was on OCT (100%), as expected given its highest detection rate, as we have previously shown. (18) This was followed by B-scan OCTA (79.5%), en face OCTA (71,8%), and clinical examination (51.3%). Interestingly, the different NVD anatomical subtypes detected on OCTA can explain the lower detection rate on fundoscopy, as we found that most of the clinically undetectable NVD resulted from subtypes 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…ese studies in principle have highlighted the comparability of OCTA with ultrawidefield FA in diagnosis and follow-up of PDR. On the other hand, Schwartz et al have found B-Scan OCTA to be the most sensitive tool assessing detection rate in NV reactivation [31]. ese results highlight the importance of taking into account both planes-en face and B-Scans when using OCTA for follow-up measurements of NV.…”
Section: Discussionmentioning
confidence: 88%